Zoombinis island odyssey [electronic resource] - Learning Company; WISSER; Riverdeep Interactive Learning Limited (Novato CA Riverdeep Interactive Learning Ltd, 2002)
"Life continued to be good for the Zoombinis. That is, until they received word about the homeland they had left behind. The dastardly Bloats had destroyed the nautral habitat and then evacuated, leaving the Zerbles and other wildlife struggling for survival. Join the Zoombinis and develop math, logic, and scientific-thinking skills on a courageous expedition to save the Zerbles
Ages 8 & up
1
Keywords: CD.ROM (Children ); Educational games; Mathematics--Study and teaching (Primary)--Juvenile software; Problem solving--Juvenile software; Science--Study and teaching (Primary)--Juvenile software